Caracterização citogenética, compostos fenólicos e genotoxicidade de Sambucus australis Cham. & Schltdl. (Adoxaceae) - Tedesco, Marília (2015)
The economic potential of the medicinal species native to Brazil is huge, rendering it important to maintain the available plant genetic diversity via studies characterizing germplasm. Between these studies, highlights the characterization meiotic and pollen viability, genotoxic and antiproliferative activitie, beyond determination of phenolic compounds. Sambucus australis Cham. & Schltdl. ( sabugueiro ) numbers among the native species with medicinal potential, being widely used in the treatment of symptoms of skin eruptions, influenzas and common colds, for its diaphoretic, anti-inflammatory and analgesic actions. The objective of the present study was to investigate the antiproliferative, genotoxic and antigenotoxic activity of aqueous extracts of two accesses of S. australis, using the Allium cepa test, and to determine the phenolic compounds present in these extracts, as well as to analyze the meiotic behavior and estimate the pollen viability of different accesses of S. australis collected in Rio Grande do Sul state. Antiproliferative, genotoxic and antigenotoxic activities were determined by assessing the effect of aqueous extracts from the inflorescences and leaves of two accesses of S. australis, at concentrations of 3 g.L-1 and 12 g.L-1, on the cellular cycle of A. cepa. High performance liquid chromatography (HPLC) was employed to determine the phenolic compounds present in the extracts. For the meiosis analysis, slides were prepared by squashing technique of the anthers removed from the flower buds. The phases of association and distribution of the chromosomes were observed and meiotic indexes determined. To estimate pollen viability, the slides were prepared by squashing the anthers, comparing three stains: 2% acetic-orcein, 2% acetic-carmine, and Alexander´s reaction. All statistical analyses of the data were performed using the Scott-Knott test (p<0.05). Results showed that the aqueous extracts of S. australis exerted antiproliferative activity on the cellular cycle of A. cepa. The extracts prepared from S. australis (12g.L-1) leaves, for both accesses, also exhibited antigenotoxic activity. Chromatographic analysis disclosed the presence of the following compounds: gallic acid, chlorogenic acid, caffeic acid, ellagic acid, rutin, quercitrin, isoquercitrin, quercetin and kaempferol. Ultimately, the accesses of S. australis studied exhibited regular meiotic behavior, gametic number n=19, meiotic index > 90% and high pollen viability, being stain Alexander´s reaction the most efficient to estimate pollen viability in the specie.